Contamination of Stream Sediment With Heavy Metals in the Awetu Watershed of Southwestern Ethiopia - Astatkie, Higemengist; Ambelu, Argaw; Mengistie, Embialle (Frontiers in Earth Science, 2021)
Surface sediment samples were collected from different streams of Awetu Watershed in southwestern Ethiopia. Sediment samples were analyzed for As, Cd, Cr, Pb, and Hg levels using inductively coupled plasma optical emission spectrometry. The heavy metal concentration ranged from 183.60 to 1102.80 mg/kg for As (mean 623.32 ± 291.65 mg/kg), 4.40 to 303.20 mg/kg for Cd (151.09 ± 111.5 mg/kg), 149.20 to 807.20 mg/kg for Cr (375 ± 212.03 mg/kg), 485.60 to 3748.80 mg/kg for Pb (2005.94 ± 954.99 mg/kg) and 3.6 to 5.6 mg/kg for Hg (4.64 ± 0.59 mg/kg). The mean heavy metal concentration in the streams followed the decreasing order of Pb > As > Cr > Cd > Hg. As, Cr and Pb are detected at high concentrations with values of 623.32, 375.00, and 2,005.94 mg/kg respectively. A low level of heavy concentration (3.6 mg/kg) was recorded for Hg. The contamination factor (CF) of all the studied heavy metals ranged from a low degree (CF < 1) to a very high degree (CF ≤ 6). Mainly, Dololo and Kito streams show a very high degree of contamination (CF ≤ 6) than Awetu and Boye streams. Specifically, As, Cd, and Cr in the Dololo and Kito streams have significantly elevated concentrations than others. Geo-accumulation index (Igeo) shows low to moderate contamination level with As, Pb, and Hg; uncontaminated to heavily contaminated by Cr; and moderate to extreme contamination by Cd. Untreated solid waste, garages and farmlands were sources of contamination. Streams receiving wastewater effluents from teaching institutions had higher heavy metal concentrations. Dumping of electronic wastes and car washing discharges also identified as another source of pollution.